EXPLORING INFORMATION AND SOLUTIONS IN ARABIC MANUSCRIPTS IN THE MIDDLE OF THE COVID-19 PANDEMIC - Uus Rustiman; Yani Rohmayani; Ade Kosasih (Yayasan Education and Social Center, 2022)
This study discusses the Badzl al-Mā'un fī Fadhl at-Thā'ūn Manuscript; Exploring Information and Solutions in Arabic Ancient Texts amid the Covid-19 Pandemic. This research not only has scientific (theoretical) use-value for philology but can be utilized by further research. Philological research, in this regard, is more of basic research that is very open to further research steps which are considered far from having practical value. A study of the Badzl al-Mā'un fī Fadhl ath-Thā'ūn Manuscript which means